Making pictorial print : media literacy and mass culture in British magazines, 1885-1918 - Hedley, Alison (Studies in book and print culture., 2021)
"At the end of the nineteenth century, print media dominated British popular culture, produced in greater variety and on a larger scale than ever before. Within decades, new visual and auditory media had ushered in a mechanized milieu, displacing print from its position at the heart of cultural life. During this period of intense change, illustrated magazines maintained a central position in the media landscape by transforming their letterpress orientation into a visual and multimodal one. Ultimately, this transformation was important for the new media cultures of the twentieth and twenty-first centuries. Making Pictorial Print recovers this chapter in the history of new media, applying concepts from media theory and the digital humanities to analyse four popular late-Victorian magazines - the Illustrated London News, the Graphic, Pearson's Magazine, and the Strand - and the scrapbook media that appropriated them. Using the concept of media literacy, these case studies demonstrate the ways in which periodical design aesthetics affected the terms of engagement presented to readers, creating opportunities for them to participate in and even contribute to popular culture. Shaped by publishers, advertisers, and readers themselves, the pages of these periodicals document the emergence of modern mass culture as we know it and offer insight into the new media of our digital present."--